Validity Of Hadith Ru‘yah ‘Al-Ṣādiqah: Implementation of Hadith Exegesis in the Encounter of Sufi Order Guides with Prophet Muhammad SAW through Dreams - Suyuti, Machmud (Institut Agama Islam Negeri Parepare, 2023)
This article examines the significance of the Qur'an and Hadith as fundamental sources of Islamic teachings, focusing specifically on the concept of ru‘yah ‘al-ṣādiqah (true dream) within the context of Sufi orders. The Hadith, serving as an explanation of the Qur'an, plays a critical role in comprehensively understanding Islamic teachings. This research particularly highlights the importance of syarḥ al-ḥadiṡ bi al-ḥadiṡ, the practice of interpreting one Hadith with another, to understand the concept of ru‘yah ‘al-ṣādiqah. In the realm of Sufi orders, ru‘yah ‘al-ṣādiqah is interpreted as a meeting with Prophet Muhammad SAW in a dream, a prerequisite for a mursyid (spiritual guide) to authorize the practice of Sufi order rituals to their disciples. The continuity of sanad (the teaching chain) from a mursyid to the Prophet is considered evidence of authenticity and blessing. The Forum Bahsul Masail Multaqa Sufi Ṭariqiyah al-Alami al-Rābi’ affirmed that meeting the Prophet through dreams or in a conscious state is a requirement for a Sufi order mursyid. The experience of waliyullah dreaming of meeting Prophet Muhammad SAW is acknowledged as a truth and a requisite for a Sufi order mursyid. This emphasizes the presence of ittiṣāl al-sanad (connectivity of the teaching chain) within the Sufi order domain. This study hypothesizes that accurate understanding of the Hadith ru‘yah ‘al-ṣādiqah and the encounters of the Prophet with mursyid through dreams are key in validating the practices and teachings within Sufi orders.